PENINGKATAN HASIL BELAJAR SISWA KELAS III PADA MATA PELAJARAN IPA MELALUI METODE DEMONSTRASI DI MI TARBIYATUL ATHFAL 1 SUMBERSARI, SRONO, BANYUWANGI - Ramiati, Eka; Faishol, Riza (INCARE, International Journal of Educational Resources, 2021)
This research aims to: ( 1 ) improve student learning outcomes class at MI Tarbiyatul Athfal 1 Sumbersari, Srono, Banyuwangi on subjects science using a method of a demonstration; ( 2 ) explain the application of a method of the demonstrations that can improve student learning outcomes on subjects science class students in MI Tarbiyatul Athfal 1 Sumbersari, Srono, Banyuwangi. This kind of research is to research a class action against learning outcomes students with the use of a demonstration. A model research and design a class action use the model kemmis & amp; taggart with research, including planning stages the implementation of the act of, observation and reflection.The act of done in two. Cycle A test subject 10 students in class iii at mi tarbiyatul athfal 1 sumbersari, srono, Banyuwangi. An analysis of data used is a technique descriptive qualitative. The result showed that an increase in student learning outcomes: characterized by of 5 students who are categorized as completed in learning ( 50 % ) increased to 8 students (80% ) of the total 10 students in a classroom with the 82,15 rerata .In 80% komulatif is students who scored above kkm required that 65 .